2017
DOI: 10.1039/c7ta03691d
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of alkene hydrogenation in carbon nanoreactors of different diameters: probing the effects of nanoscale confinement on ruthenium nanoparticle catalysis

Abstract: Exploratory, competitive hydrogenation reactions reveal the optimum level of confinement to control chemical reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 50 publications
(52 reference statements)
2
17
0
Order By: Relevance
“…Carbon nanotubes are mechanically robust, thermally and chemically stable cylinders of sp 2 ‐carbon that can be used to immobilize both molecules and nanoparticles which efficiently adsorb onto the nanotube walls and/or are encapsulated within the internal cavity of the nanotube via noncovalent interactions such as van der Waals forces . Once the catalyst is immobilized in the hollow structure, catalytic chemical reactions which occur within the accessible nanoscale space of the nanoreactor interior can benefit from enhanced rates of reactions and selectivity …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Carbon nanotubes are mechanically robust, thermally and chemically stable cylinders of sp 2 ‐carbon that can be used to immobilize both molecules and nanoparticles which efficiently adsorb onto the nanotube walls and/or are encapsulated within the internal cavity of the nanotube via noncovalent interactions such as van der Waals forces . Once the catalyst is immobilized in the hollow structure, catalytic chemical reactions which occur within the accessible nanoscale space of the nanoreactor interior can benefit from enhanced rates of reactions and selectivity …”
Section: Introductionmentioning
confidence: 99%
“…Specifically, metal nanoparticles (NPs) supported in graphitized carbon nanofibers (GNFs) catalysts have recently been used for a variety of different reactions, including platinum nanoparticles (PtNPs) in CC cross coupling reactions, IrNPs in hydrosilylations, and CuNPs in click chemistry . In a recent study, we demonstrated that RuNPs confined in GNFs result in dramatic changes to reactions with the highest observed activity and selectivity in single and competitive hydrogenations of norbornene and benzonorbornadiene compared to unconfined RuNPs supported on single‐walled carbon nanotubes (SWNTs) and commercial carbon black . PtNPs confined within GNF were also investigated in the oxygen reduction reaction (ORR) by Gimenez‐Lopez et al and outstanding electrochemical stability was observed over 50 000 cycles of ORR, with the PtNPs stabilized by the step edges significantly more strongly than commercial PtNPs on carbon black .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These nanosized containers are either synthetically produced (for instance, nano porous, tubular and hollow nanomaterials with various geometries and diameters) or they are inherently composed of nano pores and channels (for instance, proteins, lipids and zeolites, etc) 1620 . This confinement offers the control of a chemical reaction to make a particular product such as a new class of nanomaterials and/or gains a new insight into fundamental basics of physics and chemistry of the material 16,19 .…”
Section: Introductionmentioning
confidence: 99%